Acute Putrescine Supplementation with Schwann Cell Implantation Improves Sensory and Serotonergic Axon Growth and Functional Recovery in Spinal Cord Injured Rats - J. Bryan Iorgulescu; Samik P. Patel; Jack Louro; Christian M. Andrade; Andre R. Sanchez; Damien D. Pearse (Neural Plasticity)
Schwann cell (SC) transplantation exhibits significant potential for spinal cord injury (SCI) repair and its use as a therapeutic modality has now progressed to clinical trials for subacute and chronic human SCI. Although SC implants provide a receptive environment for axonal regrowth and support functional recovery in a number of experimental SCI models, axonal regeneration is largely limited to local systems and the behavioral improvements are modest without additional combinatory approaches. In the current study we investigated whether the concurrent delivery of the polyamine putrescine, started either 30 min or 1 week after SCI, could enhance the efficacy of SCs when implanted subacutely (1 week after injury) into the contused rat spinal cord. Polyamines are ubiquitous organic cations that play an important role in the regulation of the cell cycle, cell division, cytoskeletal organization, and cell differentiation. We show that the combination of putrescine with SCs provides a significant increase in implant size, an enhancement in axonal (sensory and serotonergic) sparing and/or growth, and improved open field locomotion after SCI, as compared to SC implantation alone. These findings demonstrate that polyamine supplementation can augment the effectiveness of SCs when used as a therapeutic approach for subacute SCI repair.